Effect of Periodontitis and Periodontal Therapy on Oral and Gut Microbiota - Baima, G; Ferrocino, I; Del Lupo, V; Colonna, E; Thumbigere-Math, V; Caviglia, G P; Franciosa, I; Mariani, G M; Romandini, M; Ribaldone, D G; Romano, F; Aimetti, M (Journal of dental research, 2024)
Mounting evidence indicates that periodontitis-related oral bacteria may contribute to gut microbial dysbiosis. This clinical study aimed to explore the oral-gut microbial signatures associated with periodontitis and to longitudinally evaluate the effect of periodontal treatment on the oral and gut microbial composition. Stool and saliva samples from generalized stage III/IV periodontitis patients ( = 47) were collected and analyzed by 16S ribosomal RNA gene amplicon sequencing, before and 3 mo after steps I to II of periodontal therapy. Periodontally healthy matched subjects ( = 47) were used as controls. Principal component analysis was carried out to identify oral-gut microbial profiles between periodontitis patients at baseline and healthy subjects; periodontitis samples were longitudinally compared before and after treatment. β-Diversity of gut microbial profiles of periodontitis patients before treatment significantly differed from healthy controls ( < 0.001). Periodontal therapy was associated with a significant change in gut microbiota ( < 0.001), with post-treatment microbial profiles similar to healthy volunteers. A higher abundance of , , , and was noted in fecal samples of periodontitis patients at baseline compared to healthy controls. In contrast, was the only genus more abundant in the latter. Additionally, periodontal therapy led to a parallel reduction in the salivary carriage of periodontal pathobionts, as well as gut , , , , and , to levels similar to healthy controls. Collectively, discriminating oral-gut microbial signatures of periodontitis were found. Periodontal treatment both mitigated oral dysbiosis and altered gut microbial composition, signifying potential broader implications for gastrointestinal health and disease.